The effect of education based on Systematic comprehensive Health Education and Promotion model to Health volunteers on their female clients' knowledge regarding breast cancer screening - Khadijeh Mirzaii; Shadan Nesari Ashkezari; Talaat Khadivzadeh; Mohammad taghi Shakeri (Mashhad University of Medical Sciences, 2017)
Background & Aim: Despite the importance of screening for early diagnosis of breast cancer, few women do it. Existence an indigenous educational model to promote health literacy is essential. This study attempted to determine the effect of breast cancer screening education based on SHEP model to Healthy volunteers on women's knowledge covered by Mashhad health centers  Methods & Materials: This was a quasi-experimental study with two groups: Trainers and Audients, done in two urban health centers affiliated to Mashhad district health authority, divided randomly to experimental and control centers. Six health volunteers and sixty women with random selected from each center were the sample of the study. An 8-hour workshop conformity SHEP model was conducted over two days for health volunteers in experimental group. In both centers ten women were allocated for each health volunteer, were taken a pre-test with an assessment test evaluating their knowledge about breast cancer screening, a 2-hour educational session was performed for them by health volunteers, immediately and 4 weeks after educational sessions two post-tests were taken. Research data were processed and analyzed, using Mann Whitney, Friedman, Chi Square, Fisher's exact test in SPSS statistical software, version 20 Results: The post interventional scores of knowledge were significantly higher in the experiment group (p